The Dakota Sioux experience at Flandreau and Pipestone Indian schools - Landrum, Cynthia, 1967- (University of Nebraska Press, 2019)
"'The Dakota Sioux Experience at Flandreau and Pipestone Indian Schools' illuminates the relationship of the Dakota Sioux community to the schools and larger region, as well as their long-term effort to maintain their role as Caretakers of the "sacred citadel" of their people."--